The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction - Trompet, Stella; Postmus, Iris; Warren, Helen R.; Noordam, Raymond; Smit, Roelof A. J.; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I.; Hitman, Graham A.; Munroe, Patricia B.; Rotter, Jerome I.; et al. (Frontiers in Pharmacology, 2022)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been studied in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigate whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with fixed-effects model, inverse variance weighted meta-analysis. All SNPs with p-values <5.0x 10 4 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (8 studies, n=10,769, 4,212 cases), we observed no genome-wide significant results (p<5.0x10-8). A total of 144 genetic variants were followed-up in the second stage (3 studies, n=1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. Genetic testing for predicting effects of statins on clinical events is likely no valuable tool for clinical practice.